δ15N and δ13C cycles in narwhal (Monodon monoceros) embedded teeth reveal seasonal variation in ecology and/or physiology - Shu-Ting Zhao; Cory J. D. Matthews; Cortney A. Watt (Royal Society Open Science)
Monitoring Arctic marine mammals in response to rapid climate change requires reliable longitudinal data. To obtain such data is challenging, but sequential measurements of stable isotopes (SI) from metabolically inert tissues like dentine allow for chronological reconstruction of SI data that can provide insights into whale life history, behaviour and physiology. This study examined dentine samples from narwhal embedded canines to reconstruct individual SI profiles and assess intra-annual variation in δ15N and δ13C. The individual δ15N and δ13C profiles of all 31 narwhals exhibited cyclical oscillations. The majority of δ15N and δ13C oscillations (>50%) occurred within the annual growth layer groups (GLGs), suggesting seasonal variation. The mean magnitude of SI oscillations per individual ranged from 0.4‰ to 2.5‰ for δ15N and 0.2‰ to 1.1‰ for δ13C. Such intra-annual SI oscillations may reflect variability in narwhal ecology related to environmental variation (e.g. seasonal changes in baseline SI and diet associated with narwhal migration) and/or changes in narwhal physiology (e.g. seasonal energetics), highlighting the utility of SI profiles for long-term monitoring of narwhal’s ecological and physiological responses to a changing Arctic.